Rancang Bangun Website Sistem Pengembangan Usaha Mikro dan Kecil Pada Kedai Nyoklat Klasik Delisya Delicious - Pranatawijaya, Viktor Handrianus; Christie, Sagita Amaria (Journal of Information Technology and Computer Science, 2022)
Kedai Nyoklat Classic Delisya Delicious is one of the business units engaged in beverages and snacks in the city of Palangka Raya. Based on the observations I made of this shop, at this time Kedai Nyoklat is experiencing difficulties in conveying information, because Kedai Nyoklat only uses Instagram social media to promote and is still not consistent in delivering information. Therefore, "Design and Build a Website for Micro and Small Business Development System at Kedai Nyoklat Classic Delisya Delicious" which serves as a promotional medium to introduce Kedai Nyoklat to the general public. The methodology used in designing and building this website is the waterfall method. This method was chosen because it has a sequential and organized structure so as to minimize errors that occur. This website uses Black Box Testing as a software testing method. From the results of this test, it can be concluded that "Designing a Website for Micro and Small Business Development System at Kedai Nyoklat Classic Delisya Delicious" was made with the aim of promoting the products sold to the wider community so that the income of this Nyoklat Shop will increase by attracting the interest of visitors who visit this website.